Shadow Economy: Determinants and Its Impact on Foreign Direct Investment - Heriqbaldi, Unggul; Jatmiko, Salwaa Fauziyyah (Jurnal Ilmu Ekonomi Terapan, 2024)
The shadow economy poses a significant threat to government revenue and the effectiveness of economic policies. This paper investigates the causes of the shadow economy and its influence on foreign direct investment (FDI). Our study employs the currency demand approach, a component of the indirect method, to identify the determinants of the shadow economy in a dataset covering 105 countries from 2001 to 2017. These countries are categorized into four income groups: high-income, upper-middle-income, lower-middle-income, and low-income. Parameter estimation is conducted using the Generalized Method of Moments (GMM) model, with robustness tests incorporating reference estimates from Partial Least Squares (PLS) and Fixed Effects Model (FEM). Our findings indicate that a higher GDP and lower interest rates are associated with reduced shadow economy activity. Elevated market interest rates increase the cost of funds in the informal sector, discouraging engagement in shadow economic activities due to reduced profitability. Furthermore, higher tax revenues correlate with intensified regulatory enforcement, increasing the risks associated with shadow economy involvement. A larger workforce and lower unemployment rates similarly diminish shadow economy activity. In the context of foreign direct investment (FDI), the shadow economy positively affects FDI flows when formal institutions, including legal frameworks, property rights protection, and regulatory systems, are either weak or overly burdensome. In such scenarios, economic actors may opt for informal channels like the shadow economy, offering a flexible and cost-effective alternative to the formal sector, a crucial consideration for foreign investors.